Vplivi okoljskih dejavnikov na pojavljanje in prostorsko razporeditev zobne fluoroze pri srnjadi (Capreolus capreolus L.) v vzhodni Sloveniji - Jelenko Turinek, Ida (Zbornik gozdarstva in lesarstva, 2010)
Increased concentrations of fluorides in the environment have a negative impact on different animal species, which are manifested mainly with the irregular formation of the dental hard tissue, called dental fluorosis. With the assessment of dental fluorosis in every adult roe deer shot in eastern Slovenia in 10 Hunting Management Districts in 2007 (n = 7,158), implementation of statistical analyses in raster GIS environment with high resolution (1x1 km) and cartography, we wished to: (i) establish the differences in the appearance and distribution of dental fluorosis in roe deer from different areas of eastern Slovenia; (ii) define the impact of the main sources of fluorides on the appearance and distribution of dental fluorosis; (iii) determine the most important environmental factors that have an impact on the appearance of dental fluorosis. In general, eastern Slovenia is not polluted with fluorides, while less than 1% of samples showed moderate to severe dental fluorosis; 84% of samples showed no fluorosis at all. Only inthe vicinity of the most important source of fluorides in Slovenia (aluminium smelter), there is an area with extreme fluoride pollution of the environment. The multivariate statistics revealed that the appearance and distribution of dental fluorosis are influenced primarily by: (i) the distancefrom the most important point source - (94.6% of the total variance); (ii) the age of the analysed animal (5% of the total variance); and (iii) the distance from the nearest forest edge (0.7% of the total variance), respectively.
Keywords: bioindikatorji; fluoridi; GIS; okoljski dejavniki; srnjad; zobna fluoroza